Instruction-Level Loop Perforation - Catelan, Daniela; Duenha, Liana; Santos, Ricardo; Wanner, Lucas (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2023: Anais do XXIV Simpósio em Sistemas Computacionais de Alto DesempenhoDO - 10.5753/wscad.2023.235929, 2023)
Approximate computing (AC) offers techniques ranging from application to circuit levels. AC techniques offer better performance at the cost of inaccurate results. A widely used software AC technique is loop perforation (LP). This paper presents an Instruction-Level LP (ILLP) approach that relies on approximate hardware instructions. We extended the ACCEPT compiler and SPIKE simulator workflows to generate and simulate applications with ILLP. We evaluated the technique comparing the results of precision, number of instructions, cycles, and energy consumption. ILLP achieves a 74.61% reduction in the number of instructions for the PI application, a 51.40% reduction in the number of cycles for the FFT, and an energy saving of 74.49% for the PI.